A History of Male Psychological Disorders in Britain, 1945-1980. - Haggett, Alison (London : Palgrave Macmillan UK, 2015)
This book is open access under a CC BY license and explores the under-researched history of male mental illness from the mid-twentieth century. It argues that statistics suggesting women have been more vulnerable to depression and anxiety are misleading since they underplay a host of alternative presentations of 'distress' more common in men.
Cover -- Title Page -- Copyright Page -- Table of Content -- List of Figures and Tables -- Acknowledgements -- List of Abbreviations -- Introduction -- 1 Psychological Illness and General Practice -- 2 Mental Health at Work: Misconceptions and Missed Opportunities -- 3 Men, Alcohol and Coping -- 4 Pharmacological Solutions -- 5 Special Cases: Sick Doctors and Ethnic Presentations of Psychological Illness -- Conclusion -- Appendix -- Notes -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books